Effect of the Use of an Endotracheal Tube (ETT) and Stylet versus An Endotracheal Tube (ETT) alone on first‑Attempt Intubation Success and Duration - Imran, Faisal; Mushtaq, Madeeha; Ali, Saqib; Hussain, Tanvir; Mushtaq, Sadaf; Khadim, Areeb; Kanwal, Sibgha (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the effect of the use of an endotracheal tube and stylet versus an endotracheal tube alone on first attempt intubation success and duration. Study Design: quasi-experimental study Place and Duration of Study: Critical care Department of National Hospital and Medical Center, Lahore, Pakistan from Jun to Aug 20224. Methodology: This quasi experimental study was done on 202 patients of either gender aged above 18 years, recruited from ICU of National Hospital, Lahore requiring ETT intubation. Written informed consent was taken from attendants. Demographic details of all patients were noted. Patients were divided into two Groups A (ETT+Stylet) and B (ETT only). Following parameters, SpO2 levels at start and end of intubation, total duration of intubation procedure, and success rate were noted. Results: 1st attempt success rate noted was higher for Group-A 89(88.1%) vs B-76(75.2%), and this difference was statistically significant p=0.01. Time duration to complete intubation was also calculated to be significantly low for Group A patient 16.89 ±1.42 seconds vs 22.62 ±2.21 seconds, p < 0.001. Conclusion: Our findings have suggested, that ETT+Stylet found to have more 1st-attempt success rate of intubation and it takes significantly less time to complete intubation in ICU setting, as compared when ETT used alone.